Development of an Algorithm and Mathematical Modeling for the Process of Pipeline Gas Supply with Medium Pressure Using Plastic Pipes in Order to Prevent Emergencies on the Ground - Nabievich, Musaev Marufjan; Ilkhomovna, Khodjaeva Sevarakhon; Azimzhonovich, Boboev Azizjon (European Journal of Life Safety and Stability (2660-9630), 2022)
The article describes the gas transportation of Central Asia. The calculation of the underground average pressure of the gas pipeline for strength, for pressure endurance, vibration, gas friction on the wall of the proposed polyethylene pipe, leaks, emissions into the environment and accidents is given.